Aṡar Istikhdām Uslūbay al-Tadrībī wa al-Tabādulī fī Taṭwīr al-Ḍarbatayn al-Arḍiyyatayn al-Amāmiyyah wa al-Khalfiyyah bi al-Tinnis - Mustafa, Abdullah Jalaluddin (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
This research aimed to investigate the effect of using training and alternating methods on developing the forehand and backhand groundstrokes in tennis. The experimental method was used due to its suitability to the nature of the research. This research was conducted on a sample of (20) female volunteers at the Duhok Sports Club Tennis Academy, aged (10-12) years. They were divided into two experimental groups: The first experimental group, consisting of (10) players, used the training method to develop their forehand and backhand skills, while the second experimental group used the alternating method to develop their forehand and backhand skills in tennis. The training program lasted (6) weeks, with an average of two training sessions of (90) minutes each. The program included (24) training sessions, of which (12) were using the training method and (12) were using the alternating method. In the reciprocal training method, certain variables (age, height, weight) were controlled, and the participants' forehand and backhand groundstrokes were tested. The training program was then implemented, followed by a post-test. Data were collected and statistically analyzed, leading the researcher to conclude the following: 1- Both the reciprocal and training methods had a positive impact on developing the forehand and backhand groundstrokes in tennis. 2- The results of the first group, which used the reciprocal training method, were superior to those of the second experimental group, which used the reciprocal method, in developing the forehand and backhand groundstrokes in tennis. Therefore, the researcher recommends: 1-Using the reciprocal training method due to its clear positive impact on developing the forehand and backhand groundstrokes in tennis.